Hangeshashinto-Associated Mesenteric Phlebosclerosis and Highly Atypical Adenoma Requiring Laparoscopic Right Hemicolectomy - Ryo Nishiwaki; Yasuhiro Inoue; Masataka Sugao; Natsuko Sugimasa; Tetsuya Hamaguchi; Midori Noji; Kenji Takeuchi; Yoshiyuki Ito; Toshio Kato; Taro Yasuma; Corina N. D’Alessandoro-Gabazza; Esteban C. Gabazza; et al. (Diagnostics, 2024)
Mesenteric phlebosclerosis is a rare ischemic colonic disorder caused by impaired venous drainage. Its prevalence is higher in East Asia, where herbal medicine is widely used. Treatment remains controversial. A 76-year-old woman who had taken Hangeshashinto, an herbal medicine, for 11 years was admitted for endoscopic treatment of high-grade dysplasia in the ascending colon. She had diarrhea and mesenteric phlebosclerosis diagnosed by abdominal computed tomography at age 71. At age 75, small polyps were detected in the ascending colon. A subsequent study revealed an increase in polyp size to 15 mm. Endoscopic mucosal resection failed to remove the lesion. A biopsy showed high-grade dysplasia with possible colon cancer risk. Conservative therapy did not improve mesenteric phlebosclerosis-related diarrhea; therefore, a laparoscopic right hemicolectomy was performed. Intraoperatively, the cecum was adherent to the abdominal wall and the right ovary. The specimen showed high-grade dysplasia in the mucosa and severe submucosal fibrosis. No metastasis was observed. This case shows the link between mesenteric phlebosclerosis and high-grade dysplasia in the ascending colon. Endoscopic mucosal resection was unsuccessful in removing the tumor. Endoscopic submucosal dissection was an alternative, but its safety in mesenteric phlebosclerosis-affected colonic segments remains uncertain. A laparoscopic right hemicolectomy was performed.